2001
DOI: 10.1063/1.1390487
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microstructure on electrical properties of diluted GaNxAs1−x formed by nitrogen implantation

Abstract: Structural studies of GaAs implanted with N or co-implanted with other elements showed that, in addition to typical post-implant defects, small voids were present in the implanted region in such materials. Comparison of the microstructure found in these layers with electrical results indicates that these voids are responsible for the low activation efficiency of N implanted into GaAs. The results show that the N-induced enhancement of the donor activation efficiency can be achieved only in void-free region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…A high density of nanometer-sized bubbles, which are probably filled with nitrogen gas, is also seen in this region [27]. This highly defective area is then followed by a region containing the "end-off range" defects that extends to a depth of ~0.5 µm.…”
Section: Crystalline Structure Of N + -Implanted Gaas Layers Processementioning
confidence: 92%
See 1 more Smart Citation
“…A high density of nanometer-sized bubbles, which are probably filled with nitrogen gas, is also seen in this region [27]. This highly defective area is then followed by a region containing the "end-off range" defects that extends to a depth of ~0.5 µm.…”
Section: Crystalline Structure Of N + -Implanted Gaas Layers Processementioning
confidence: 92%
“…2(b) demonstrate that using the PLM-RTA method, the N incorporation efficiency is ~50% (slightly lower for the high dose case), over five times higher than that observed in samples synthesized by RTA alone. This can be attributed to the extremely short melt duration (~200 nsec) and regrowth process that promotes N substitution in the As subslattice and inhibits the formation of nitrogen related voids, which have recently been observed in samples formed by N + -implantation followed by RTA only [27].…”
Section: Nitrogen Activation Efficiencymentioning
confidence: 99%
“…37 Such a drastic improvement can be attributed to the extremely short melt duration (~2×10 -7 s) and re-growth process that promotes N substitution in the As site and inhibits the formation of nitrogen related voids. 38 In addition to the enhanced N incorporation, the dilute nitride layers synthesized by N + -implantation followed by PLM-RTA were also found to be thermally stable up to annealing temperature >950°C. This improved sample synthesis technique provides a convenient and reliable method, in addition to conventional epitaxial growth techniques, 2,4,12 for preparing large variety of dilute nitride samples.…”
Section: Samplesmentioning
confidence: 99%
“…In the course of optimizing the annealing conditions in these studies, it was found that, in GaNAs formed in this way, the substitutional N As is thermally unstable at temperatures higher than 850°C and will precipitate to form N-related voids. 38 Most recently, we have shown that pulsed laser melting (PLM) of N-implanted III-Vs dramatically improves the incorporation of N on the group-V element site. 39,40 In PLM, the near surface absorption of a single intense laser pulse instantaneously melts the implant-damaged or amorphized layer.…”
Section: Samplesmentioning
confidence: 99%
“…The value of the band gap of the laser melted layers does not change significantly even at RTA temperature of 950ºC, suggesting that the substitutional nitrogen (N As ) in these layers appears are thermally stable. We speculate that the extremely short duration of the laser melting and regrowth process inhibits the formation of nitrogen related voids, which have recently been observed in samples formed by N + -implantation followed by RTA only [24]. The process of rapid melting and solidification may result in a complete local rearrangement of the atom sites leading to the formation of strong Ga-N bonds, thus stabilizing N atoms on the anion sites.…”
mentioning
confidence: 99%